Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Terhadap Profesi Akuntan Publik - Ni Luh Ayu Sekar Suryani; Armiani; Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to find out the factors that influence accounting students' interest in the public accounting profession. The independent variables of this research are professional training, personality, job market considerations, parental influence and the dependent variable is accounting students' interest in the public accounting profession. This type of research uses quantitative methods with an associative approach and collects primary data using questionnaire techniques which are measured using a Likert scale. The population of this study were accounting undergraduate students at PTS throughout Mataram City, class of 2019. Sampling used a saturated sampling technique. The sample used was 121 respondents. The analysis technique used is multiple linear analysis with SPSS 25. The results of this research show that professional training and personality have no effect on accounting students' interest in the public accounting profession. Meanwhile, job market considerations and parental influence have a positive effect on accounting students' interest in the public accounting profession. The R Square figure shows a value of 51.7% so that 48.3% is influenced by other variables.